2023
DOI: 10.1371/journal.pone.0282264
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, risk perception, and coping strategies among healthcare workers in Egypt during the COVID-19 pandemic

Abstract: Background Coronavirus disease-19 emerged in December 2019. Healthcare workers were exposed to this highly infectious virus during the pandemic and suffered several social and psychological consequences, such as anxiety, psychological distress, and burnout. Objectives To assess the psychological distress, anxiety, depression, coping strategies, risk perception, and attitude toward interprofessional teamwork among Egyptian healthcare workers during the COVID-19 pandemic. Methods We conducted a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…According to our results, from the perspective of medical workers, they are advised to seek mental health screening 43 . Additionally, attending health campaigns such as mindfulness-based stress practice and small-group programs may also be affective 6 .…”
Section: Discussionmentioning
confidence: 88%
“…According to our results, from the perspective of medical workers, they are advised to seek mental health screening 43 . Additionally, attending health campaigns such as mindfulness-based stress practice and small-group programs may also be affective 6 .…”
Section: Discussionmentioning
confidence: 88%
“…Sociodemographic factors, such as gender and age have been previously related to a higher risk 38 . Female sex has been associated with a increased risk of mental disorders in several studies analyzing the impact of the COVID-19 pandemic on the mental health of HCWs 43 47 . A recent meta-analysis conducted by Lee and colleagues including 401 studies, has reported higher odds of probable mental health disorders in women, in particular depression, anxiety, PTSD and insomnia 48 .…”
Section: Discussionmentioning
confidence: 99%
“…This stress is increased due to their pre-existing limited access and resources, imposed by the colonial system, and their management of the new coronavirus, in certain vulnerable subgroups (health care workers) who are likely to require psychological interventions). Indeed significant associations were observed between attitude toward interprofessional teamwork, gender, marital status, occupation, work experience, current work location (clinics), spiritual influences, perceived competence, difficulties in daily life, income level, confidence in individual instincts, level of control over aspects of resilience, provision of COVID-19 patient care, history of COVID-19 testing, history of COVID-19 testing or infection, and availability of mental health support in the workplace ( 7 , 8 , 14 , 16 , 19 , 24 28 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the response to COVID-19, frontline health workers are inevitably at risk of SARS-CoV-2 infection ( 7 , 14 16 ). They have a 3.4 times higher risk of contracting COVID-19, a higher risk of death compared to people living in the general community ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation